2016
DOI: 10.15408/aiq.v8i1.2513
|View full text |Cite
|
Sign up to set email alerts
|

Application of Theory Reasoned Action in Intention to Use Islamic Banking in Indonesia

Abstract: Application of Theory Reasoned Action in Intention to Use Islamic Banking in Indonesia. This paper investigates the constructs of Theory of Reasoned Action (TRA), and Theory of Planned Behavior (TPB) (attitude, subjective norm, religion, knowledge, pricing, and government support) on customer behavioral intention and Islamic banking selection. This research using Partial Least Square Structural Equation Modeling with variables such as: attitude, subject norm, religion, knowledge and government support, and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
38
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 6 publications
11
38
1
1
Order By: Relevance
“…They indicated that religiosity influences attitudes and behaviour, and attitude influences intention. Furthermore, Reni and Ahmad () found that religion had a significant and positive relationship to intention. Religious values or symbols can play an important role in the daily functioning of society.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…They indicated that religiosity influences attitudes and behaviour, and attitude influences intention. Furthermore, Reni and Ahmad () found that religion had a significant and positive relationship to intention. Religious values or symbols can play an important role in the daily functioning of society.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…The TRA has been applied in different areas of studies including Islamic finance (Fauziah, Taib, Ramayah, & Abdul Razak, 2008;Bidin et al, 2009;Reni & Ahmad, 2016), innovativeness and adoption (Gumel & Othman, 2013) and intention (Muhammad, Haneef, & Muhammed, 2016). The present study extends the application of this theory to an investigation on intentions to patronise Islamic banking.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The present study extends the application of this theory to an investigation on intentions to patronise Islamic banking. Although, some studies have explored a similar area in other countries (Echehabi & Oladokun, 2012;Reni & Ahmad, 2016), studies in this area are still scanty in the Nigerian context. Therefore, this study adapted the TRA model to provide an adequate explanation on intention to patronise Islamic banking in Nigeria.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Hijab fashion means fashion whose properties and processing techniques include raw materials, handling, the use of various methods from beginning to end, always in reference to Islamic law (Sharia). Prior research (for example, [3], [4], [7][8][9][10], [12]) found that there is significant relationship between consumers' knowledge of Halal products and their purchase intention. Hence, knowledge of Hijab fashion supply becomes an imperative part of Muslim consumers's intentions to purchase Hijab fashion.…”
Section: Consumers' Knowledgementioning
confidence: 99%